Modeling Dengue Vector Dynamics under Imperfect Detection: Three Years of Site-Occupancy by Aedes aegypti and Aedes albopictus in Urban Amazonia - Padilla-Torres, Samael D.; Ferraz, Gonçalo; Luz, Sérgio Luíz Bessa; Zamora-Perea, Elvira; Abad-Franch, Fernando (PLoS ONE, 2013)
Aedes aegypti and Ae. albopictus are the vectors of dengue, the most important arboviral disease of humans. To date, Aedes ecology studies have assumed that the vectors are truly absent from sites where they are not detected; since no perfect detection method exists, this assumption is questionable. Imperfect detection may bias estimates of key vector surveillance/control parameters, including site-occupancy (infestation) rates and control intervention effects. We used a modeling approach that explicitly accounts for imperfect detection and a 38-month, 55-site detection/non-detection dataset to quantify the effects of municipality/state control interventions on Aedes site-occupancy dynamics, considering meteorological and dwelling-level covariates. Ae. aegypti site-occupancy estimates (mean 0.91; range 0.79-0.97) were much higher than reported by routine surveillance based on 'rapid larval surveys' (0.03; 0.02-0.11) and moderately higher than directly ascertained with oviposition traps (0.68; 0.50-0.91). Regular control campaigns based on breeding-site elimination had no measurable effects on the probabilities of dwelling infestation by dengue vectors. Site-occupancy fluctuated seasonally, mainly due to the negative effects of high maximum (Ae. aegypti) and minimum (Ae. albopictus) summer temperatures (June-September). Rainfall and dwelling-level covariates were poor predictors of occupancy. The marked contrast between our estimates of adult vector presence and the results from 'rapid larval surveys' suggests, together with the lack of effect of local control campaigns on infestation, that many Aedes breeding sites were overlooked by vector control agents in our study setting. Better sampling strategies are urgently needed, particularly for the reliable assessment of infestation rates in the context of control program management. The approach we present here, combining oviposition traps and site-occupancy models, could greatly contribute to that crucial aim. © 2013 Padilla-Torres et al.
Keywords: Virus Rna; Aedes Aegypti; Aedes Albopictus; Breeding; Dengue; Disease Carrier; Disease Transmission; Egg Laying; Geographic Distribution; Health Survey; Human; Infestation; Molecular Dynamics; Nonhuman; Public Health Problem; Seasonal Variation; Urban Area; Vector Control; Aedes; Animals; City; Dengue; Dengue Virus; Ecology; Environment; Female; Geography; Insect Control; Male; Population Dynamics; Procedures; Reproduction; Season; Statistical Model; Temperature; Transmission; Virology; Aedes; Animalss; Cities; Dengue; Dengue Virus; Ecology; Environment; Female; Geography; Insect Control; Insect Vectors; Likelihood Functions; Male; Population Dynamics; Reproduction; Seasons; Temperature